Scanning electron microscopy of biomaterials - McKinlay, K.J.; Scotchford, C.A.; Grant, D.M.; Oliver, J.M.; King, John R.; Brown, Paul D. (Institute of Physics Publishing, 2004)
A comparison of conventional high vacuum scanning electron microscopy (HVSEM), environmental SEM (ESEM) and confocal laser scanning microscopy (CLSM) in the assessment of cell-material interactions is made. The processing of cells cultured for conventional HVSEM leads to the loss of morphological features that are retained when using ESEM. The use of ESEM in conjunction with CLSM of the labeled cytoskeleton gives an indication of changes to the cell morphology as a consequence of incubation time and substrate surface features.